The right to food: widely acknowledged and poorly protected - Pinstrup-Andersen, Per; Nygaard, David F.; Ratta, Annu (International Food Policy Research Institute, 1995)
The right to food has always been recognized as a valid and fundamental right of the individual. In the absence of food, other political and economic rights and freedoms are meaningless. Global food supplies have for many years been more than adequate to feed the world's population. Nonetheless, hunger and malnutrition are still painful realities. Does hunger represent a failure of states to serve their populations? Would the situation be different if food was a legal right of every individual in the world? The international community has for decades struggled over creating a right to food for the individual, and over defining it in legally enforceable terms. Although they continue to endorse the right to food, states have not translated this right into specific legal obligations, nor are there any effective national or international mechanisms to supervise the implementation of this right. 2020 Vision research indicates that although the global food supply may continue to be sufficient to feed the world to the year 2020, the incidence of malnutrition and food insecurity will remain high unless current national and international policies and priorities are changed. Perhaps this then is a time for the international community to examine its fundamental objective in development. If the individual really is the central subject of development, then a concerted shift may be needed in economic development policies to provide each individual with the most rudimentary of human needs: food.